Globalisation : can the state strike back? - CABLE, Vincent (1996)
Notes that with globalisation - the international integration of communications and economies - nation states are losing some of their traditional roles, viz: control over flows of information and perhaps, the definition of cultural values; many aspects of independent economic management; and, the capacity significantly to shift the distribution of income and wealth. Points out that despite globalisation, the nation state still holds sway in many fields. These include migration control, the distribution of income, enhancement of national competitiveness, and 'position nationalism'.